2004
DOI: 10.1111/j.1744-6171.2004.00049.x
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Associated Factors in Children With Attention Deficit Hyperactivity Disorder

Abstract: Children with ADHD are more inclined to experience depressive symptoms than are healthy children. To plan appropriate interventions, nurses evaluating and working with children with ADHD should always consider a possible coexistence of depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
8
1
2
Order By: Relevance
“…In the current study, twins with ADHD demonstrated higher levels of depressive symptomatology compared to their non-ADHD co-twins. These findings concur with previous studies which have also indicated that children and adolescents with ADHD are more likely to experience increased levels of depressive symptoms compared to controls without ADHD (Kitchens et al, 1999;LeBlanc & Morin, 2004). However, this study extends from these findings as the significant differences between the twins can be attributed to the effects of unique environmental factors (Phelps et al, 1997).…”
Section: Discussioncontrasting
confidence: 37%
See 1 more Smart Citation
“…In the current study, twins with ADHD demonstrated higher levels of depressive symptomatology compared to their non-ADHD co-twins. These findings concur with previous studies which have also indicated that children and adolescents with ADHD are more likely to experience increased levels of depressive symptoms compared to controls without ADHD (Kitchens et al, 1999;LeBlanc & Morin, 2004). However, this study extends from these findings as the significant differences between the twins can be attributed to the effects of unique environmental factors (Phelps et al, 1997).…”
Section: Discussioncontrasting
confidence: 37%
“…Studies employing clinical based samples have shown that children and adolescents with ADHD are more likely to be diagnosed with mood disorders such as depression and anxiety than comparison children (Angold & Costello, 1993;Biederman et al, 1991). Studies involving community samples have also linked ADHD with increased levels of depressive symptoms if not a diagnosis of depression per se (Jensen et al, 1993;Kitchens et al, 1999;LeBlanc & Morin, 2004). A recent twin study examining separation anxiety and generalized anxiety in DZ twins discordant for ADHD also identified the twin with ADHD at greater risk of these disorders than the nonaffected twin (McDougall et al, 2006).…”
mentioning
confidence: 99%
“…Dentro de los síntomas depresivos, el que se encontró con mayor frecuencia puede corresponder a ambas patologías, ya que la falta de concentración es criterio diagnóstico de ambas patologías (6,13).…”
Section: Discussionunclassified
“…Sin embargo, no todos los investigadores han obtenido estos resultados (13,14). Además, la depresión es el diagnóstico mas frecuente en pacientes con intento suicida (10), por esta razón es importante investigar si los niños con TDAH y síntomas depresivos pueden tener mayor riesgo.…”
Section: Introductionunclassified
“…This estimate was conservative compared with fi ndings from LeBlanc and Morin [26]. Data from the Children's Depression Inventory revealed that 7-to 12-year-old children with ADHD had signifi cantly more symptoms of depression than did their non-ADHD counterparts.…”
Section: Adhd and Comorbid Mdd In Children And Adolescentsmentioning
confidence: 92%